Avaliação do desempenho térmico de tijolos ecológicos em Aracaju/SE por meio de simulação computacional - Dunel, Maria Paula (2020)
The growing urbanization and industrialization of modern societies has generated large-scale production of solid waste, thus constituting a proliferation of these, a problem worldwide, with immediate consequences for public health and the environment. Urban solid waste must be managed and controlled in order to reduce its volume and dangerousness, minimizing the damage caused by environmental pollution and the impacts on people's health. Currently, the most common waste control techniques are recycling and composting. Such techniques are known as tools that enable the use of waste, in this context, the use of recyclable materials in civil construction has been growing day by day. However, in Brazil, no approach was found regarding any material for civil construction based on solid household waste, such as ecological brick. In this work, the thermal performance of the ecological brick, a brick with low environmental impact, was analyzed. The main objective of the study was to verify the effectiveness of the ecological brick in terms of thermal performance. The methodological strategy consisted of measuring the thermal performance of two reference models with solid ceramic brick masonry, therefore, changes were made to the equivalent wall of the reference model, such as the addition of coating mortar and white paint (α = 0.20). Soon, the replacement of solid ceramic brick masonry by brick masonry with ecological ones produced with stabilized RSUs in order to compare the indoor air temperature values of buildings. The measurement was performed by computer simulation with the EnergyPlus® software using the full-scale prototypes, on a typical summer day (December 21) in the state of Sergipe. In the results, it was observed that in the simulated buildings with an equivalent wall of ecological bricks, a minimum difference of internal air temperature of no more than 0.14 ° C was obtained in the most critical of the day, time at 3 pm, in comparison simulated buildings with an equivalent wall of solid ceramic bricks. In the simulations carried out with the equivalent wall with coating mortar and white paint, there was no difference, even at the most critical time of the day. However, it is observed that there was a significant improvement in the thermal performance of masonry, with a difference in the internal air temperature of reaching 1.84 ° C in relation to uncoated bricks and white paint (α = 0.20). Therefore, for better thermal performance of buildings in the bioclimatic zone-8, it is recommended that the fence made of ecological bricks be coated with mortar and have its facade painted with a white color of absorbance equal to 0.20. Thus, there was a change in the values of thermal resistance and thermal delay related to the behavior of masonry in different building environments. Thus, material thickness, specific heat, absorbance and thermal conductivity were the properties that most influenced the building's thermal performance. It was found that the ecological brick, due to its greater thickness, greater specific heat and lower thermal conductivity, achieved a greater optimization of the building's thermal performance compared to solid ceramic brick. But this is when the ecological brick is compared only without the application of the common mortar for laying the brick.